Le carnaval fantastique : Monstrueuse mascarade et (p)acte de lecture - Moreau, Dennis (Romanica Silesiana)
The aim of the present work is to consider the articulation between the carnival and the literary fantastic, perceived as a dynamic subversion of reality able to arouse fear. Carnival’s imagery and fantastic strategies as metamorphoses can be considered like deviation from consensus reality, and allow to understand more specifically how the fantasy literature works and its differences from mimetic fiction. Literary techniques like autorepresentation or intertextual references highlight the text’s fictionality, and conduct a literary reflection on the poetics of fantastic prose fiction. The fantastic is not trying to represent the world as we know it, and the pleasure of reading is here closely linked to the notions of willing suspension of disbelief or secondary belief. Key words: fantastic fiction, carnival, fear, metafiction, autorepresentation, author-reader contract, willing suspension of disbelief